Pengaruh Konsumsi Susu Coklat terhadap Daya Tahan Kardiorespirasi Atlet Cabang Olahraga Permainan BPPLOP Jawa Tengah: Effect of Chocolate Milk Consumption on Cardiorespiratory Endurance of Central Java BPPLOP Games Athletes - Jayaputra, Vitta Maitri Budhi; Putriningtyas, Natalia Desy (Amerta Nutrition, 2024)
Background: Sports games with aerobic and anaerobic energy systems require muscular and cardiovascular endurance, as well as high dietary intake. Carbohydrate loading before training can maximize glycogen storage and carbohydrate oxidation, thereby increasing performance. Chocolate milk powder, as much as 45 g, contains 55 g of carbohydrates, contributing to 6-8% of total carbohydrate needs. Objectives: Analyzing the effect of chocolate milk consumption on muscle endurance and maximum oxygen volume capacity (VO2 Max) in sports athletes at the BPPLOP Central Java Student Sports Education and Training Center. Methods: Research with pretest-posttest control design with the same sample with a washout period. A sample of 47 athletes was taken using a total sampling technique, all used as a control group and treated for 6 days with 200 ml 2 hours before training. Measurement of endurance using the multistage fitness test. Test the difference in effect before and after treatment using the Paired Samples T-Test, while testing the difference between control and treatment groups using Mann Whitney. Results:  There was a significant effect between before and after consuming chocolate milk on increasing muscle endurance by 2150.64 ± 420.72 to 2314.47 ± 400.14 m and VO2 Max capacity by 53.95 ± 5.96 to 56.30 ± 5.62 ml/kg/minute with a p-value=0.00. There was a significant difference between the consumption of placebo and chocolate milk in increasing muscle endurance by 163.83 m and VO2 Max capacity by 2.34 ml/kg/minute with a p-value=0.00. Conclusions: Carbohydrate loading by consuming 45 g of chocolate milk in 200 ml containing 55 g of carbohydrates before training for 6 days can affect increasing muscle endurance and VO2 Max capacity in sports athletes.